Українське чумацтво та одеське біндюжництво в контексті розвитку логістики та туризму в Україні - Смирнов, Ігор; Smyrnov, Igor (Східноєвропейський національний університет імені Лесі Українки, 2016)
Розкрито значення українського чумацтва як предтечі для розвитку сучасної логістики в Україні. Висвітлено особливості чумацтва в Україні як суспільно-економічного явища, яке змінювалося протягом століть від функцій воїна-торговця, торговця-посередника між виробником та споживачем і, нарешті, до фурщика, візника зі своїми фаховими особливостями. Раскрыто значение украинского чумачества как предтечи для развития современной логистики в Украине. Освещены особенности чумачества в Украине как общественно-экономического явления, которое изменялось на протяжении веков от функций воина-торговца, продавца-посредника между производителем и потребителем и, наконец, к фурщику, извозчику – со своими этнокультурными особенностями. Revealed the importance of Ukrainian Chumatstvo as a founder of Ukrainian Logistics in Ukraine. Shown the peculiarities of Chumatstvo in Ukraine as a socio-economic phenomenon, which for centuries was changing its features from warrior-merchants to merchant – intermediaries between producers and consumers, and finally to cab – with their ethno-cultural characteristics. Revealed mapping features of Chumaks’ activity in Ukraine. Revealed logistical and geographical features of Chumatstvo in Ukraine. The first ones concern Chumak’s transport charakteristics, particularly their carts («mazhas») and draft animals – oxens. Second part reveals the geography of Chumaks routs and transportation of salt and other goods – in Ukraine and abroad. Defined the basic routes of Chumaks transport, which were key roads in Ukraine in XVI–XIX (first half) centuries. Among them – Norman – Greek way, Black, Voloh and Chumak’s ways. These pathways made by Chumaks had those characteristics that, first, they were made along rivers, second, skipped settlements, and third, were mostly located in the steppe of Ukraine. As a modern road network in Western Europe was formed under the Ancient Roman system of roads so the road map of modern Ukraine has as its basis the Chumak routes.
Ukrainian Chumatstvo and Odessa Вinduzhnystvo in Сontext of Logistics and Tourism Development in Ukraine
Keywords: українське чумацтво; фахові (транспортно-логістичні) особливості; географічний вимір; одеські біндюжники; Ukrainian сhumakcraft; sectoral (transport and logistics) characteristics; geographical dimension; bendyuzhniki of Odessa